Role for targeted resection in the multidisciplinary treatment of metastatic gastrointestinal stromal tumor - Kim, Bradford J. (Transl Gastroenterol Hepatol, 2019)
The management of advanced gastrointestinal stromal tumors (GISTs) has evolved in the modern era due to the discovery of c-kit mutations and the development of tyrosine kinase inhibitors (TKIs). Until the advent of TKIs such as imatinib, the median survival reported for patients with advanced GIST was 19 months. Although surgery is the treatment of choice for resectable primary GIST, its role in cases of recurrence and metastasis remains to be unclear. This review outlines the potential beneficial role of repeat surgical resection in the multidisciplinary treatment of advanced GIST in the era of TKIs.